MicroRNAs, fibrotic remodeling, and aortic aneurysms - Milewicz, Dianna M. (The Journal of clinical investigation, 2012)
Aortic aneurysms are a common clinical condition that can cause death due to aortic dissection or rupture. The association between aortic aneurysm pathogenesis and altered TGF-β signaling has been the subject of numerous investigations. Recently, a TGF-β-responsive microRNA (miR), miR-29, has been identified to play a role in cellular phenotypic modulation during aortic development and aging. In this issue of JCI, Maegdefessel and colleagues demonstrate that decreasing the levels of miR-29b in the aortic wall can attenuate aortic aneurysm progression in two different mouse models of abdominal aortic aneurysms. This study highlights the relevance of miR-29b in aortic disease but also raises questions about its specific role.